Lip morphometry in 600 North Indian adults: a data base study for sexual dimorphism. (January 2015) - Goel, Archana; Patnaik, VVG; Puri, Nidhi
The study comprised lip morphometry of 600 North Indian adults (300 males and 300 females). The aim of the study was to create base data of various linear and vertical measurements of the upper and lower lips and width of the mouth. This standard may serve as a guideline for sexual dimorphism as well as for restoration or enhancement of esthetic and plastic surgery for the lips in the north Indian population, which will enable the surgeon to offer a better cosmetic result. Prior informed written consent from all the subjects was obtained. The exclusion and inclusion criteria for the subjects were predefined. The analysis shows the sexual dimorphism in most parameters of lips being greater in males. The results were compared with the available data for north white Americans, Malays, Malaysian Indians, Italians, western Indians and Caucasians. In the population under study, the measurements differ in all dimensions with Malays, Italians and Caucasians and show resemblance to the Malaysian Indians. Knowledge of the proportion between the upper and lower lips helps in surgical correction of the region. This study highlights the applied significance of observations of the present study to forensic, namely racial and sex dimorphic, criteria of identification.